Influence of Students’ Attitudes, Interests, Mathematical Background, and Perception of Teacher Behaviour on Physics Achievement in Secondary Schools - Edidiong E. Ukoh (Journal of Research in Environmental and Science Education, 2025)
This study investigates the influence of students’ attitudes, interests, mathematical backgrounds, and perceptions of their teachers’ behavioral patterns on their academic achievement in physics among senior secondary school students in Ibadan, Nigeria. Using an ex post facto research design, data were collected from 200 students through a Physics Achievement Test (PAT) and the Attitude, Interest, Mathematical Background, and Students’ Perception Questionnaire (AIMSQ). Descriptive and inferential statistical methods, including multiple regression analyses, were employed to evaluate relationships between the independent variables and students’ physics achievement. The findings revealed that students’ attitudes toward physics had a significant positive relationship with their achievement (β = .369, t = 4.000, p = .0001), as did their interest in physics (β = .785, t = 3.035, p = .0028). Students’ perceptions of their teachers’ behavioral patterns also showed a moderate but significant relationship with achievement (β = .183, t = 2.179, p = .0307). However, students’ mathematical backgrounds were not a statistically significant predictor of physics performance (β = .046, t = .496, p = .6206). The results underscore the importance of fostering positive attitudes and sustained interest in physics, enhancing teacher-student interactions, and providing supportive learning environments to improve students’ academic performance. Recommendations for improving physics education outcomes include professional development for teachers, integration of practical applications, strengthening mathematical skills, and enhancing motivational programs for students. The study concludes by emphasizing the need for a multifaceted approach to address the factors influencing students’ performance in physics and promote national scientific literacy and technological advancement.